Mitochondrial respiratory capacities are not linked to individual variation in hypoxia tolerance and standard metabolic rate in European seabass Dicentrarchus labrax - Elisa Thoral; Julie Nati; Jean‐Baptiste Quémeneur; Léann Lozac'h; Germain Salou; Alain Vergnet; Mathieu Besson; Marc Vandeputte; François Allal; Karine Salin; David J. McKenzie; Loïc Teulier (Journal of Fish Biology, 2026)
In hypoxic environments, fish attempt to regulate their metabolic rate as oxygen levels in the water decline. Individuals that have low energy requirements for maintenance – standard metabolic rate (SMR) – are expected to have higher hypoxia tolerance, measured as the critical water oxygen saturation threshold (S crit ) below which they cannot regulate SMR. These whole animal traits may, in turn, be linked to aspects of individual mitochondrial oxidative metabolism that underpin SMR. We therefore investigated, in European seabass Dicentrarchus labrax , whether inter‐individual variation in SMR and S crit , measured by whole animal respirometry, was correlated with elements of mitochondrial metabolism in liver and heart, measured by high resolution respirometry (HRR). Among the 96 fish studied, inter‐individual variation in S crit was dependent upon variation in SMR. However, there was no evidence for correlations between SMR or S crit and individual mitochondrial respiratory capacities. Our results indicate that individual variation in complex whole animal traits of respiratory metabolism cannot always be linked to variation in subcellular mitochondrial phenotypes.

Environmental consequences of genetic improvement of growth and fillet yield in gilthead seabream: A life cycle assessment from breeding to plate - Sophie De Montmorillon; Simon Pouil; Marc Vandeputte; Jean-Sébastien Bruant; Jérôme Bugeon; Ivonne Acosta-Alba; Cédric Pincent; Benjamin Quittet; Mathieu Besson; Joël Aubin; Pierrick Haffray (Aquaculture, 2026)

Corrigendum to “Genomic selection for individual feed efficiency in the European seabass: Response to selection on efficiency, commercial traits and sex” [Aquaculture Volume 595, Part 2, 30 January 2025, 741682]. - François Allal; Mathieu Besson; Emilie Delpuech; Chloé Barrier-Loiseau; Alain Vergnet; Franck Morell; Marie-Odile Blanc; Stéphane Lallement; Frédéric Clota; François Ruelle; Marc Vandeputte (Aquaculture, 2025)

Genomic selection for individual feed efficiency in the European seabass: Response to selection on efficiency, commercial traits and sex - François Allal; Mathieu Besson; Emilie Delpuech; Chloé Barrier-Loiseau; Alain Vergnet; Franck Morell; Marie-Odile Blanc; Stéphane Lallement; Frédéric Clota; François Ruelle; Marc Vandeputte (Aquaculture, 2025)

Anemone bleaching impacts the larval recruitment success of an anemone-associated fish - Marc Besson; William E. Feeney; Camille Gache; Duncan A. O’Brien; Cécile Berthe; Zara-Louise Cowan; Rohan M. Brooker; Vincent Laudet; David Lecchini (Coral Reefs, 2023)
In marine environments, mutualisms such as those between corals or sea anemones and their algal symbionts (Symbiodiniaceae) play a key role for supporting surrounding biodiversity. However, as the breakdown of the mutualism between corals and/or anemones and Symbiodiniaceae (i.e. bleaching) become increasingly frequent and severe, the risk of losing the additional species that rely on them may also increase. While the effects of anemone bleaching on the biology and ecology of anemone-associated fishes have been the subject of recent research, relatively little is known about the impacts that anemone bleaching might have on the recruitment of larval fish. Here, we report that climate change-induced anemone bleaching impairs a secondary mutualism between anemones and an anemone-associated fish species, the threespot dascyllus ( Dascyllus trimaculatus ). Field-based monitoring over a 1-year period showed anemones that bleached experienced decreased recruitment of larval D. trimaculatus compared to those that did not bleach, with abundances of newly settled D. trimaculatus three times lower in bleached versus unbleached anemones. A visual choice experiment showed that this pattern is associated with fish being less attracted to bleached anemones, and a predation experiment demonstrated that fish associated with bleached anemones experienced higher mortality compared to those associated with unbleached anemones. These results suggests that the decreased recruitment of D. trimaculatus observed in bleached anemones may be driven by hampered pre-settlement (habitat selection) and post-settlement (survival to predation) processes for larval D. trimaculatus in bleached hosts. This study highlights the risk of cascading mutualism breakdowns in coral reefs as conditions deteriorate and stresses the importance of protecting these mutualisms for the maintenance of coral reef biodiversity.

Towards the fully automated monitoring of ecological communities - Marc Besson; Jamie Alison; Kim Bjerge; Thomas E. Gorochowski; Toke T. Høye; Tommaso Jucker; Hjalte M. R. Mann; Christopher F. Clements (Ecology Letters, 2022)
High‐resolution monitoring is fundamental to understand ecosystems dynamics in an era of global change and biodiversity declines. While real‐time and automated monitoring of abiotic components has been possible for some time, monitoring biotic components—for example, individual behaviours and traits, and species abundance and distribution—is far more challenging. Recent technological advancements offer potential solutions to achieve this through: (i) increasingly affordable high‐throughput recording hardware, which can collect rich multidimensional data, and (ii) increasingly accessible artificial intelligence approaches, which can extract ecological knowledge from large datasets. However, automating the monitoring of facets of ecological communities via such technologies has primarily been achieved at low spatiotemporal resolutions within limited steps of the monitoring workflow. Here, we review existing technologies for data recording and processing that enable automated monitoring of ecological communities. We then present novel frameworks that combine such technologies, forming fully automated pipelines to detect, track, classify and count multiple species, and record behavioural and morphological traits, at resolutions which have previously been impossible to achieve. Based on these rapidly developing technologies, we illustrate a solution to one of the greatest challenges in ecology: the ability to rapidly generate high‐resolution, multidimensional and standardised data across complex ecologies.

Local sonic activity reveals potential partitioning in a coral reef fish community - Frédéric Bertucci; Katy Maratrat; Cécile Berthe; Marc Besson; Ana Sofia Guerra; Xavier Raick; Franck Lerouvreur; David Lecchini; Eric Parmentier (Oecologia, 2020)

No Effect of Polystyrene Microplastics on Foraging Activity and Survival in a Post-larvae Coral-Reef Fish, Acanthurus triostegus - Hugo Jacob; Arthur Gilson; Chantal Lanctôt; Marc Besson; Marc Metian; David Lecchini (Bulletin of Environmental Contamination and Toxicology, 2019)

Predation drives recurrent convergence of an interspecies mutualism - William E. Feeney; Rohan M. Brooker; Lane N. Johnston; James D. J. Gilbert; Marc Besson; David Lecchini; Danielle L. Dixson; Peter F. Cowman; Andrea Manica (Ecology Letters, 2019)
Mutualisms are important ecological interactions that underpin much of the world's biodiversity. Predation risk has been shown to regulate mutualism dynamics in species‐specific case studies; however, we lack studies which investigate whether predation can also explain broader patterns of mutualism evolution. We report that fish‐anemone mutualisms have evolved on at least 55 occasions across 16 fish families over the past 60 million years and that adult body size is associated with the ontogenetic stage of anemone mutualisms: larger‐bodied species partner with anemones as juveniles, while smaller‐bodied species partner with anemones throughout their lives. Field and laboratory studies show that predators target smaller prey, that smaller fishes associate more with anemones, and that these relationships confer protection to small fishes. Our results indicate that predation is likely driving the recurrent convergent evolution of fish‐anemone mutualisms and suggest that similar ecological processes may have selected convergence in interspecies interactions in other animal clades.

Complete and rapid reversal of the body color pattern in juveniles of the convict surgeonfish Acanthurus triostegus at Moorea Island (French Polynesia) - Marc Besson; Pauline Salis; Vincent Laudet; David Lecchini (Coral Reefs, 2018)

Whole-Brain High-Resolution Structural Connectome: Inter-Subject Validation and Application to the Anatomical Segmentation of the Striatum - Pierre Besson; Nicolas Carrière; S. Kathleen Bandt; Marc Tommasi; Xavier Leclerc; Philippe Derambure; Renaud Lopes; Louise Tyvaert (Brain Topography, 2017)

Disrupted downstream migration behaviour of European silver eels (Anguilla anguilla, L.) in an obstructed river - Marc L. Besson; Thomas Trancart; Anthony Acou; Fabien Charrier; Virgile Mazel; Antoine Legault; Eric Feunteun (Environmental Biology of Fishes, 2016)